A cohort study of infant feeding practices and maternal breastfeeding problems in a rural area of Sichuan Province, PR China - Tang, Li (Curtin University, 2013)
Breastfeeding has been consistently shown to be the appropriate feeding method for infants. The benefits of breastfeeding for the health of infants and women are well documented. To achieve optimal growth, development and health, the World Health Organization (WHO) recommends exclusive breastfeeding for the first six months of life and continued breastfeeding thereafter with appropriate complementary foods.Breastmilk has been the only source of nutrition for the newborn infants for thousands of years in China. But since the late 1970s, China has experienced a rapid decline in prevalence and duration of breastfeeding. In response to Chinese government’s support for the Baby Friendly Hospital Initiative (BFHI) and the introduction of some regulation of the marketing of breastmilk substitutes, increase in the breastfeeding rates has been observed around the country since 1992. However, the exclusive breastfeeding rates to 6 months postpartum are still low in most places and few provinces had achieved the national target of 80% exclusive breastfeeding rate at 4 months by 2000. Despite its negative influence on infants’ health, early introduction of complementary foods is a common phenomenon across China. There has been little research exploring the factors that influence the early complementary feeding in China. Experiencing breastfeeding problems, such as cracked and sore nipples, insufficient milk supply and mastitis is common amongst lactating mothers. Very few studies have documented the incidence of mastitis or have determined its influential factors among Chinese mothers.Information about infant feeding practices in the rural area of Sichuan province is limited. No previous prospective cohort studies on infant feeding practices have been undertaken in Sichuan Province, China. The objectives of this study were to document the use of prelacteal feeds and investigate factors associated with early initiation of breastfeeding among mothers in Jiangyou, Sichuan Province; investigate the prevalence and duration of breastfeeding up to 12 months postpartum; identify determinants of breastfeeding at discharge and discontinuing breastfeeding before 12 months postpartum; examine the incidence of breastfeeding problems mother experienced within 6 months postpartum; explore determinants of lactation mastitis; document the prevalence of premature introduction of complementary foods and its associated factors.; and recommend possible strategies for improving breastfeeding prevalence in rural areas of Sichuan Province, China.